Importance of urban parks in psychological recovery: An experiment with young adults from Poland - Kobyłka, Agata; Korcz, Natalia (Quaestiones Geographicae, 2025)
Recently, attention has been focused on the role of urban green spaces in promoting people’s health and well-being. There are many studies indicating the need and necessity of expanding green infrastructure to have a positive impact on urban dwellers’ mental health. Many of them are conducted in spring and summer. This study is to determine how a walk in three different urban locations (the city park centre, the outskirts of the city park and the city centre) during the ‘golden’ autumn affects the well-being of young adult Poles. The research was conducted in 2022 in the Saski (Saxon) Garden and its immediate vicinity (Lublin, Poland). In order to check how walks in three different locations affect the psychological recovery of respondents, four types of psychometric questionnaires were used: the Positive and Negative Affect Scale (PANAS), Profile of Mood States (POMS), Subjective Vitality Style (SVS), and Restorative Outcome Scale (ROS), which respondents completed before and after a given type of walk. As a result of walking around the city park (both on its outskirts and near the fountain), the respondents’ levels of tension, depression, anger, fatigue, and disorientation decreased. During the walk by the fountain, these drops were larger. However, after walking along a city street, the level of vigour was falling; it increased in the park and decreased when walking along a city street. The differences in the results (Δ = post-test – pre-test) of all tests examining the POMS mood state profile in various forms of walking turned out to be statistically significant. The results of tests measuring regeneration (ROS), vitality (SVS) and positive mood (PANAS positive) of those walking in the city park increased. During the walk by the fountain, these increases were more considerable compared to the walk along the edge of the park. The respondents’ regeneration, vitality and level of positive mood decreased in a city street. These results were statistically significantly different. For the test measuring negative mood (PANAS negative), we observed an increase in the results after a walk along a city street, a decrease regarding a walk by the fountain and a slight increase in the case of a walk on the outskirts of the park. However, these differences are not statistically significant. The results indicate that walks conducted in various parts of the park in autumn have a positive impact on the psychological recovery of young people. It is therefore important to ensure access to green and blue infrastructure in urban areas.